The analysis of mental health awareness constructs in college students during the Covid-19 pandemic based on Rasch Model application - Lestari, Sumi; Rahmawati, Intan; Faizah, Faizah; Risqi, Purnama Miftaqhul; Feraihan, Rania (Universitas Negeri Padang, 2021)
Mental health awareness is a condition when individuals are aware of the importance of mental health in maintaining their positive psychological well-being. Awareness involves prevention of mental problems, identifying mental problems, and self-managing in any possibilities of mental distuption. A way to maintain mental health awareness is to obtain knowledge or information related to disorders, management, and prevention of mental health problems through literacy. Meanwhile, Lack of mental health literacy have been identified as major obstacles for the promotion of mental health and early intervention during this pandemic era. This study aims to develop a measuring instrument by testing the validity and reliability of mental health awareness through literacy during the COVID-19 pandemic towards college students using the Rasch Model approach. The subjects of this study were male and female, college students aged 18 – 25 years and Indonesian citizens. This research was conducted on 307 subjects. The results of the research showed that the mental health awareness scale using Mental Health Literacy Questionnaire is a reliable and valid measuring instrument (α = 0.844) during the COVID-19 pandemic by using the Rasch Model approach and compared to the classical theory of mental health awareness. There are 21 valid items and 8removed items with no any dimensions are eliminated.